EVALUASI PEMAHAMAN SISWA MAN 1 BANYUMAS TERHADAP ANCAMAN PHISHING, MALWARE, DAN EVIL TWIN PASCA SOSIALISASI - Alviendra Putra Setiawan; Aziz Saputra Ramadon; Isma Bela; Rizqi Gilang Saputra; Nihlatul Jannah; Darso (Abdi Jurnal Publikasi, 2026)
The growth of internet technology in Indonesia has been accompanied by a significant rise in cybercrimes, such as online fraud, phishing, and data breaches. High school students are a particularly vulnerable group due to their limited understanding of digital security. To mitigate these risks, a community service program featuring interactive digital security education was conducted for 10th-grade students at MAN 1 Banyumas on April 29, 2026, comprising three main stages: preparation, implementation, and evaluation. The material was presented through a combination of theory and illustrative practical demonstrations covering threats—such as phishing,